Language learning strategies of students at different levels of speaking proficiency - Cabaysa, Carissa C.; Baetiong, Lourdes R.
This causal-comparative study aimed to examine the use of language learning strategies by high school students when speaking in class, and factors affecting such strategy use. Seventy sophomore students at a public school were observed, interviewed and asked to answer a 19-item language learning strategy checklist. Results show strategy use to follow this order: metacognitive, social/affective, and compensation strategies. Subjects were classified using an adaptation of the ACTFL proficiency guidelines. Intermediate and novice speakers were further observed and made to complete retrospection statements. The f-test was used to compare strategy use of the two groups while Chi-square values were computed to compare the groups? combined strategies based on retrospection statements. Results indicate significant differences between groups in the level of frequency at which metacognitive strategies were used and at which strategies were orchestrated. These factors were shown to influence strategy use: achievement in school, attitudes towards speaking English, task at hand, subject area, topic of discourse, and teacher?s techniques in allocating turns to speak and easing tension among learners asked to use the second language. Data suggest that students could further improve their speaking abilities if they would gain knowledge about learning strategies. Awareness of terms referring to various strategies would enable them to monitor the effectiveness of their strategy use and help them develop autonomy in learning English.
Originally presented as the author's thesis; University of the Philippines, 2008.
Keywords: English language -- Philippines -- Usage; English language -- Spoken English -- Study and teaching (Secondary) -- Philippines; Oral communication -- Study and teaching (Secondary) -- Philippines